2005
DOI: 10.1111/j.1540-8159.2005.00223.x
|View full text |Cite
|
Sign up to set email alerts
|

Severe Left Ventricular Systolic Dysfunction Increases Atrial Fibrillation After Ablation of Atrial Flutter

Abstract: After an AFL ablation, the incidence of Afib is increased, and the probability of remaining free of Afib is decreased, when severe LVSD is present, independent of a prior history of Afib. This finding may have implications for optimal patient selection for AFL ablation, and the use of adjunctive therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
0
2
1
Order By: Relevance
“…Ideally, patients with a higher baseline risk for developing newly diagnosed AF after cAFL ablation should be identified by risk factors, in order to direct resources for a more intense follow-up of these patients. Although some prior studies have identified such risk factors, including age [13], left ventricular dysfunction [1,14,15], left atrial dilatation [2,16] and arterial hypertension [1], these were not consistent across studies [17]. In our study, we only identified coronary artery disease as a significant predictor for recurrent AF or AT.…”
Section: Discussioncontrasting
confidence: 67%
“…Ideally, patients with a higher baseline risk for developing newly diagnosed AF after cAFL ablation should be identified by risk factors, in order to direct resources for a more intense follow-up of these patients. Although some prior studies have identified such risk factors, including age [13], left ventricular dysfunction [1,14,15], left atrial dilatation [2,16] and arterial hypertension [1], these were not consistent across studies [17]. In our study, we only identified coronary artery disease as a significant predictor for recurrent AF or AT.…”
Section: Discussioncontrasting
confidence: 67%
“…Informed consent was obtained from all patients. As described previously, 12 a 20‐pole catheter, with regular 2–10 mm spacing (Duo‐Dec Super Lrg Curl, Daig Corp., Minnetonka, MN, USA) was placed with the distal tip in the mid‐coronary sinus, spanning the isthmus, and with the proximal part in the high right atrium (Fig. 1).…”
Section: Methodsmentioning
confidence: 99%
“…Stellate Ganglion Block (SGB), a cervical sympathetic blockade, has been widely used to treat some refractory arrhythmia storms. 12 , 13 Studies have shown that blocking or resecting the stellate ganglion can inhibit the occurrence and maintenance of Atrial Fibrillation (AF), possibly by regulating the autonomic and immune systems. 7 , 14 However, the reported changes in cardiac function with LSGB in the literature have been contradictory.…”
Section: Introductionmentioning
confidence: 99%